A short linear motif in scaffold Nup145C connects Y-complex with pre-assembled outer ring Nup82 complex. Issue 1 (December 2017) - Teimer, Roman; Kosinski, Jan; von Appen, Alexander; Beck, Martin; Hurt, Ed
Abstract Nucleocytoplasmic transport occurs through nuclear pore complexes (NPCs), which are formed from multiple copies of 30 different nucleoporins (Nups) and inserted into the double nuclear membrane. Many of these Nups are organized into subcomplexes, of which the Y-shaped Nup84 complex is the major constituent of the nuclear and cytoplasmic rings. The Nup82–Nup159–Nsp1 complex is another module that, however, is only assembled into the cytoplasmic ring. By means of crosslinking mass spectrometry, biochemical reconstitution, and molecular modeling, we identified a short linear motif in the unstructured N-terminal region ofChaetomium thermophilum Nup145C, a subunit of the Y-complex, that is sufficient to recruit the Nup82 complex, but only in its assembled state. This finding points to a more general mechanism that short linear motifs in structural Nups can act as sensors to cooperatively connect pre-assembled NPC modules, thereby facilitating the formation and regulation of the higher-order NPC assembly. The Nup82–Nup159–Nsp1 complex, which plays a key role in mRNA export, is recruited late during the process of nuclear pore complex (NPC) assembly. Here the authors combine crosslinking mass spectrometry, biochemical reconstitution and molecular modeling to gain insights into the mechanism of Nup82 recruitment to the NPC.